Degunking Linux - Smith, Roderick (Degunking Ser., 2005)
Annotation Linux has grown in popularity and is increasingly being adopted by home users and others who laud this nearly un-crashable, free operating system. But setting up a Linux OS can be tricky and time consuming. And managing a Linux system can be even more difficult if you don't have the right knowledge. Degunking Linux expertly shows readers how to save time (and money) by performing a number of important degunking tasks. With Degunking Linux's easy 12-step program, users will learn what Linux gunk is, how to keep their Linux desktop clean and organized, how to better manage personal and system-related files, how to make applications ran their best, how to get gunky and incompatible drivers and hardware to run smoothly, how to protect their precious data from dangerous viruses and hackers, how to clean up and improve Linux's security features, and much more. Linux users will learn the causes of sluggish performance and how to apply smart solutions to improve overall system performance.